Enhanced infectivity of bovine viral diarrhoea virus (BVDV) in arginase-producing bovine monocyte-derived macrophages - Barone, Lucas Jose; Cardoso, Nancy; Mansilla, Florencia Celeste; Castillo, Mariangeles; Capozzo, Alejandra (Taylor & Francis, 2025)
Macrophages are important cells of the innate immunity that play a major role in Bovine Viral Diarrhoea Virus (BVDV) pathogenesis. Macrophages are not a homogenous population; they exist in different phenotypes, typically divided into two main categories: classically (pro-inflammatory) and alternatively activated (anti-inflammatory) or M1 and M2, respectively. The role of bovine macrophage phenotypes on BVDV infection is still unclear. This study characterized the interaction between BVDV and monocyte-derived macrophages (Mo-Mφ) collected from healthy cattle and polarized to an M1 or M2 state by using LPS, INF-γ, IL-4, or azithromycin. Arginase activity quantitation was utilized as a marker of the M2 Mo-Mφ spectrum. There was a significant association between arginase activity and the replication rate of BVDV strains of different genotypes and biotypes. Inhibition of arginase activity also reduced BVDV infectivity. Calves treated with azithromycin-induced Mo-Mφ of the M2 state produced high levels of arginase. Interestingly, azithromycin administered in vivo increased the susceptibility of macrophages to BVDV infection ex vivo. Mo-Mφ from pregnant dams and calves produced higher arginase levels than those from non-pregnant adult animals. The increased infection of arginase-producing alternatively activated bovine macrophages with BVDV supports the need to delve into a possible leading role of M2 macrophages in establishing the immune-suppressive state during BVDV convalescence.